PEMODELAN DAN ANALISA PRODUKSI KERAJINAN BAMBU UMKM PRINX MAS DENGAN MENGGUNAKAN ALJABAR MAX-PLUS - Yonantha, Krisma; Pranata, Franciscus Budi; Andy Rudhito, Marcellinus (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2024)
Craft production activities have a lead time so they are detrimental to entrepreneurs in terms of time and energy. To optimize production time, max-plus algebra modeling is required. This research aims to model and analyze the production process of bamboo bag and basket crafts in order to determine the periodic schedule and optimal production time. This research uses mixed methods, namely a combination of quantitative and qualitative research. Data collection was carried out using interviews and literature study. Data analysis was carried out using data integration techniques. The research results show that the periodic production time is 720 minutes and the optimal time to complete 1 production unit is 74 hours 33 minutes. This research can be developed by applying max-plus algebra to other bamboo craft products or developing a model with the possibility of disruption to the production cycle.